Sustainable supercapacitor electrodes based on preagglomerated carbon onions and a green binder. (September 2022) - Bauer, Christian; Bilican, Abdurrahman; Braxmeier, Stephan; Reichenauer, Gudrun; Krueger, Anke
Abstract: Supercapacitors play a major role in the field of energy storage. However, the production of highly efficient and durable supercapacitors using sustainable materials remains a challenge. Herein, we report on a green approach for the production of thin film binder electrodes for electric double layer capacitors (EDLCs) based on onion-like carbon. The active material obtained by high temperature treated detonation nanodiamond offers a specific surface area of 527 m 2  g −1 after an additional activation step. The key to facilitate the electrode manufacturing for this active material was the introduction of an agglomeration step of the carbon nano-onions which qualified them for the usage of plant-based carboxymethyl cellulose (CMC) as binder. The new types of electrodes were successfully tested in a supercapacitor full cell setup and benchmarked against electrodes relying on conventional fluorinated polymer (PVDF) as binder. The green electrodes provide about 22% higher specific capacitance of 56 F g −1 at a similar durability over more than 5000 cycles, combining sustainable production with excellent performance. Graphical abstract: Image 1